2021
DOI: 10.1038/s41598-021-94070-2
|View full text |Cite|
|
Sign up to set email alerts
|

Skin tolerant inactivation of multiresistant pathogens using far-UVC LEDs

Abstract: Multiresistant pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) cause serious postoperative infections. A skin tolerant far-UVC (< 240 nm) irradiation system for their inactivation is presented here. It uses UVC LEDs in combination with a spectral filter and provides a peak wavelength of 233 nm, with a full width at half maximum of 12 nm, and an irradiance of 44 µW/cm2. MRSA bacteria in different concentrations on blood agar plates were inactivated with irradiation doses in the range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…The SLR's results demonstrate a concentration of studies [3,8,17,[21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40] in this scientific field. Of these studies, all found some level of decontamination effectiveness.…”
Section: Human Healthmentioning
confidence: 76%
See 2 more Smart Citations
“…The SLR's results demonstrate a concentration of studies [3,8,17,[21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40] in this scientific field. Of these studies, all found some level of decontamination effectiveness.…”
Section: Human Healthmentioning
confidence: 76%
“…Of these studies, all found some level of decontamination effectiveness. In terms of disinfection (at least three log-reduction), we have seven studies [3,24,[33][34][35][36][37][38] indicating it. Meanwhile, ten studies [8,17,21,23,[28][29][30][31][32]39] indicate elimination of biological indicators (sterilization) or growth inhibition.…”
Section: Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…However its potential for inducing DNA damage in the skin and eye (2,3) has limited its direct use in occupied indoor spaces. By contrast, there is now compelling evidence that far-UVC radiation, commonly defined as wavelengths between 200 nm and 235 nm, is likely to be safer for direct human exposure (4)(5)(6)(7)(8), and also exhibits similarly or greater antimicrobial activity against both surface and airborne microbes (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The combination of efficacy and safety suggests far-UVC may have broad applicability to provide continuous air disinfection even while humans are present (11,18).…”
Section: Introductionmentioning
confidence: 99%
“…Germ reduction as well as skin tolerance of the two wavelengths 222 nm and 233 nm were tested on germ carrier plates and skin models ex vivo/in vitro at different doses. Complete germ reduction takes place from 40 mJ/cm 2 (Glaab et al 2021 ). Based on these doses, irradiation studies were performed on intact excised human skin and reconstructed human skin (RHS) models.…”
Section: Introductionmentioning
confidence: 99%